Smoking and vaping patterns during pregnancy and the postpartum: A longitudinal UK cohort survey. (December 2021) - Bowker, Katharine; Lewis, Sarah; Ussher, Michael; Naughton, Felix; Phillips, Lucy; Coleman, Tim; Orton, Sophie; McRobbie, Hayden; Bauld, Linda; Cooper, Sue
Highlights: Between 16% and 23% of pregnant smokers and ex-smokers vape during pregnancy. Most pregnant vapers also continue to smoke (dual use). Vaping habits of exclusive vapers is stable during pregnancy and the postpartum. A third of dual users in early pregnancy are exclusively smoking in the postpartum. Abstract: Introduction: There is limited information about longitudinal patterns of vaping during pregnancy and the postpartum. We describe the prevalence, frequency, and reasons for vaping throughout pregnancy and postpartum. We also describe temporal patterns in pregnant women's vaping. Methods: A longitudinal cohort study across England and Scotland, with questionnaires in early pregnancy (8–24 weeks gestation), late pregnancy (34–38 weeks) and 3 months postpartum. A total of 750 women, aged 16 years or over, who were either current smokers, vapers or had smoked in the 3 months before pregnancy, were recruited between June and November 2017. Results: Vaping prevalence was 15.9% (n = 119/750) in early pregnancy: 12.4% (n = 93/750) were dual users and 3.5% (n = 26/750) exclusive vapers. Late pregnancy vaping prevalence was 17.8% (n = 68/383): 12.5% (n = 48/383) were dual users and 5.2% (n = 20/383) exclusive vapers. Postpartum vaping prevalence was 23.1% (n = 95/411): 14.6% (n = 60/411) were dual users and 8.5% (n = 35/411) exclusive vapers. The most frequently reported reason to vape among all vapers was to quit smoking. A total of 316 women completed all three surveys: 2.6% (n = 8/316) were exclusive vapers in early pregnancy with most remaining exclusive vapers postpartum (n = 6/8, 75%). Of the 11.5% (n = 35/316) dual users in early pregnancy, 31.4% (n = 11/35) were exclusive smokers by the postpartum. Conclusion: Vaping prevalence was between 15.9% and 23.1% during pregnancy and the postpartum period, and the majority were dual users. Vaping habits of exclusive vapers remains stable throughout pregnancy and the postpartum. However, the vaping habits of dual users varies, with a third exclusively smoking in the postpartum.